Estéticas del entorno urbano : la experiencia de visualización de a ciudad - Ramon, Ricard (2018)
The communication raises a set of aesthetic reflections and educational im¬plications that result from the analysis of a series of works by students in nursery, pri¬mary and secondary schools, with a common goal: to create a personal narrative of the city and urban environment in which they live